A comparative assessment of minimum wage employment in Europe - Paul Redmond; Bertrand Maître; Séamus McGuinness; Konstantina Maragkou (The Economic and Social Research Institute (ESRI), 2021)
Using data for 2017 and 2018, this report provides a comparative analysis of minimum wage employment in Ireland, relative to a selection of other European countries with a statutory minimum wage. We estimate that just under 10 per cent of employees in Ireland were on the minimum wage during this time. This compares to an average incidence of 10.5 per cent among the countries studied, ranging from a high of almost 16 per cent in Portugal, to just 2 per cent in Belgium.
Keywords: 330; Mindestlohn; Arbeitskräfte; Vergleich; EU-Staaten